Pregnant women’s knowledge and practice of preventive measures against COVID-19: a study from Mysore city, Karnataka, India - Shivanagappa, Mamatha; Bhavana, Yerva Sai; Chandrashekarappa, Smitha Malenahalli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The presently ongoing COVID-19 pandemic has not spared any segment of society including pregnant women. It is absolutely essential that pregnant mothers and their caregivers be fully aware of accurate facts about COVID-19. Objective of this study was to assess the knowledge and practice of preventive measures against COVID-19 infection among pregnant women of Mysore City. Methods: This was a cross sectional study, conducted among pregnant women attending prenatal care at a tertiary care centre. Data was collected using a validated questionnaire administered via google form to consenting pregnant women. The variables assessed were knowledge about aetiology, mode of spread and preventive measures to protect against COVID-19. Data was also collected on socio-demographic characteristics, which included age, parity, marital status, residence, occupation, participant’s education, husband’s education. Results: Out of the 93 responders, majority 71 (76.3%) were in the age group 20-30 years. 17 (18.3%) were in the 30-40 years age group. Regarding number of children 41 (44.1%) had one child 16 (17.2%) had 2 children and 32 (34.3%) were primigravida. With respect to educational status 70 (75.26%) were having graduate degree. 19 (20.4%) were non graduates, but had completed high school. Educational level of the husbands of the respondents was along similar lines with 62 (66.66%) having completed graduation, and 28 (30.1%) had completed high school. 91(97.8%) respondents were correct in identifying virus as the cause of COVID-19. 88 (94.6%) rightly chose mode of spread by sneezing or cough. 1 (0.1%) respondent wrongly indicated that injections were the mode of spread. Main symptoms cough and fever were correctly identified by 80 (86%) respondents. The practice of preventive medicine was low with respect to all aspects of COVID prevention. Only 27 (29.7%) were following frequent handwashing recommendation. Only 26 (28.6%) were following staying indoors advise. 28 (30.8%) of the respondents were wearing masks. However, 82 (90.1%) were following at least one of the preventive measures. Conclusions: The knowledge levels of pregnant women were satisfactory However this was not translated into practice by majority of the respondents.